Media exposure and English language proficiency levels. A Comparative Study in Iceland and Spain - García Ortega, Sergio, 1976- (2011)
Abstract The aim of this essay is to study the status of English in Iceland and Spain. In order to achieve this goal, a comparative study of the media of both countries in terms of exposure is performed. As a result, it is suggested that Icelanders are considerably more exposed to English by the media than their Spanish counterparts.In addition, their education systems,regulations and government policies on English teaching are described. It is found that the Spanish education system devotes more time to English teaching than the Icelandic one. Add to this, Spain has more aggressive policies for improving competence in English. However, Icelandic students are expected to achieve higher proficiency levels. Therefore, it seems likely that due to higher exposure to English media Icelanders have better proficiency levels. Unfortunately, more empirical evidence is needed to state this as a fact. Thus the relationship between proficiency gained at school and proficiency gained by exposure to the media is a question worthy of further study.